Marketing within the Boundaries of Psychology: What influences the Choice Whether to go for International Education? - Hudaverdi, Huda; Yankova, Yuliya (International Review of Management and Marketing, 2016)
Procurement of international educational services is caused by the special social importance of education in life of modern society, namely realization of such functions by it, as broadcasting and dissemination of culture in society, socialization, social selection, social and cultural change of society in general, and in life of the specific person, in particular. Research objective: theoretical justification and empirical studying of international procurement of educational services as social and psychological phenomenon. For validation of a hypothesis and the solution of objectives the following methods of research were used: theoretical analysis of literature, content analysis of documents, modeling, supervision, methods of polls (conversation, questionnaire). The theoretical importance of work is expressed in development of the complete social and psychological concept of procurement of educational services in system of international education. And also in a contribution to development of social psychology of marketing and economic psychology; in the field of studying of international educational services as social and psychological phenomenon of economic consciousness and behavior of consumers; in the social and psychological analysis and psychological definition of such initially economic categories, as "advance", "demand", "educational service"; in the field of the theoretical and empirical analysis of groups of consumers of educational services, in development of psycho-diagnostic tools on a problem, in a contribution to an imagology as new interdisciplinary area of scientific knowledge. Keywords: marketing, procurement, open education, international education, psychological factors. JEL Classifications: I23, M16, M31